OPTIMIZATION OF THE TECHNOLOGICAL PROCESS OF PRODUCTION OF A HOUSING PART BASED ON THE USE OF CNC MACHINES (Web of Teachers: Inderscience Research, 2024)
The article is devoted to the development of a rational technological process for manufacturing the housing of a hydraulic distributor using CNC (computer numerical control) machines. The main objectives of the study are to reduce the manufacturing cost of the part and increase labor productivity.